A study of treatment outcomes of liver abscess in a rural tertiary care centre - Reddy, Pooja; K., Ashwin; Srinivasan, N.; Halbhavi, Manjush Ramesh (International Surgery Journal, 2019)
Background: Liver abscess is a cavity resulting from suppuration following invasion and multiplication of microorganisms. In tropical countries like India, pyogenic and amoebic liver abscesses are common clinical problems and an important cause of mortality and morbidity. Approach in management has changed with advances in radiological interventions. Image guided percutaneous drainage is nowadays increasingly used as treatment modality with high success rate. This study was undertaken to know the efficacy of various modalities of treatment (conservative and minimally invasive). Methods: This was a descriptive prospective observational study done at PES Institute of Medical Sciences and Research, Kuppam for a period of 2 years. A set of inclusion and exclusion criteria were defined and followed. Initial assessment, basic investigations with specific investigations (Ultrasonography-USG) were done. Relevant treatment modality was given and patients were followed up for a period of 1 month. Results: A total of 72 patients were included in this study. Majority of the patients were between the age groups of 31 to 50 years with male predominance. The most common presenting symptoms were fever and pain abdomen. Success rate was 83.3% with Percutaneous needle aspiration (PNA) and 90% with Percutaneous (pigtail) catheter drainage (PCD). Conclusions: Image guided modalities of treatment (PNA and PCD) have decreased the need for surgical procedures which are associated with higher rate of morbidity and mortality. These procedures have also decreased the complications of liver abscess like rupture, sepsis and are also cost-effective.